2022
DOI: 10.1001/jamadermatol.2022.1863
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Brodalumab Levels and Therapy Outcomes in Patients With Psoriasis Treated With Brodalumab

Abstract: IMPORTANCE Given the possible treatment modalities in psoriasis management, little is known about whether drug monitoring is associated with response rate. OBJECTIVE To determine whether drug monitoring is associated with response to brodalumab therapy.DESIGN A multicenter case series study of patients with psoriasis treated with brodalumab whose treatment with previous IL-17A inhibitor therapy failed. Patients were recruited from the Departments of Dermatology at Gentofte and Aarhus University Hospitals, Denm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The systemic exposure of brodalumab has been shown to be lower in patients with a higher body weight [ 43 ]. Additionally, an association between body weight, brodalumab serum levels and clinical response has been reported [ 44 , 45 ]. A phase II trial reported declining PASI response rates with increasing body weight [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The systemic exposure of brodalumab has been shown to be lower in patients with a higher body weight [ 43 ]. Additionally, an association between body weight, brodalumab serum levels and clinical response has been reported [ 44 , 45 ]. A phase II trial reported declining PASI response rates with increasing body weight [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ixekizumab, another human monoclonal antibody, inhibits the inflammatory response mediated by IL-17A binding to the IL-17A receptor (IL-17AR), whereas brodalumab can specifically block the IL-17 receptor. Extensive clinical studies have shown that ixekizumab and brodalumab are beneficial and used by the FDA in adults with moderate to severe plaque psoriasis (114,124). Emerging evidence hints that the therapeutic interventions on IL-17A may be a promising treatment strategy in ND patients.…”
Section: Targeting the Il-17a/il-17ar Axismentioning
confidence: 99%
“…For SEC, our group found a minimal effective C t of 33.2 μg/ml and proposed a target C t of 39.1 μg/ml corresponding with 92.7% probability of achieving an absolute PASI ≤2 or reduction in PASI of ≥90% 24 . For the other biologics, data suggest either the presence of an exposure‐response association or show conflicting results; or data are lacking 25–38 …”
Section: Introductionmentioning
confidence: 99%
“…24 For the other biologics, data suggest either the presence of an exposure-response association or show conflicting results; or data are lacking. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] Here, we present a cohort of IL-17i-treated Pso patients, followed up in a monocentric, academic, Pso-dedicated, integrated care setting, named PsoPlus. 39 Our objectives were to (1) present IL-17i effectiveness, (2) report on treatment modifications and (3) describe the utility of C t measurements during clinical practice.…”
mentioning
confidence: 99%